Analisis Komparasi Harga Saham Syariah pada Perusahaan Makanan dan Minuman yang Terdaftar Di ISSI/JII Periode Sebelum Covid, Saat Covid, dan Sesudah Covid (2018-2023) - Juliana, Putri; Ainol, Ainol; Prasetyandari, Cici Widya (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The COVID-19 pandemic has disrupted global economic stability, including the capital market sector. This study aims to analyze the differences in sharia stock prices of food and beverage companies listed on ISSI and JII across three periods: before the pandemic (2018–2019), during the pandemic (2020–2021), and after the pandemic (2022–2023), as well as to evaluate their recovery patterns. A quantitative approach with descriptive-comparative analysis was employed. Data were obtained from the Indonesia Stock Exchange reports and company financial statements. Data analysis began with a normality test using the Shapiro-Wilk method and a homogeneity of variance test using Levene’s Test. Based on the assumption tests, One-Way ANOVA was used to examine the differences in average stock prices across the periods. The results show significant differences in sharia stock prices among the three periods, particularly between during and after the pandemic. These findings indicate that the food and beverage sector demonstrated relatively strong resilience during the crisis and experienced positive recovery post-pandemic. The study recommends this sector as a stable sharia investment alternative in times of economic uncertainty and encourages companies to continue innovating and adapting to changing consumption patterns.